Elevated Plasma Levels of sCD14 and MCP-1 Are Associated With HIV Associated Neurocognitive Disorders Among Antiretroviral-Naive Individuals in Nigeria. (1st June 2020) - Jumare, Jibreel; Akolo, Christopher; Ndembi, Nicaise; Bwala, Sunday; Alabi, Peter; Okwuasaba, Kanayo; Adebiyi, Ruxton; Umlauf, Anya; Cherner, Mariana; Abimiku, Alash'le; Charurat, Man; Blattner, William A.; et al.
Abstract : Background: Mononuclear cells play key roles in the pathogenesis of HIV-associated neurocognitive disorders (HAND). Limited studies have looked at the association of markers of monocyte activation with HAND in Africa. We examined this association among HIV-1–infected patients in Nigeria. Method: A total of 190 HIV-infected treatment-naive participants with immune marker data were included in this cross-sectional study. Plasma levels of soluble CD14 (sCD14), soluble CD163, monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α), and neopterin were measured. Demographically adjusted T scores obtained from a 7-domain neuropsychological test battery were generated, and functional status was assessed using activities of daily living questionnaire. Participants were classified as unimpaired, having asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND), or HIV-associated dementia (HAD) in line with the "Frascati" criteria. Results: Thirty-two participants (16.8%) had ANI, 14 (7.4%) had MND, whereas none had HAD. In multivariable linear regression analyses, after adjusting for age, gender, education, CD4 count, and viral load, mean levels of sCD14 were higher among those with ANI and MND as compared with the unimpaired ( P = 0.033 and 0.023, respectively). Similarly, the mean level of MCP-1 was greater among those with HAND as compared with the unimpaired ( P = 0.047). There were also trends for higher levels of sCD163 and TNF-α among females with MND in univariable analyses. Conclusions: Levels of monocyte activation markers correlate with the severity of impairment among individuals with HAND. The mechanisms that underlie these effects and the potential role of gender require further study.